Analysis of DNA Binding and Nucleotide Flipping Kinetics Using Two-Color Two-Photon Fluorescence Lifetime Imaging Microscopy - Robinson,T; Valluri,P; Kennedy,G; Sardini,A; Dunsby,C; Neil,MAA; Baldwin,GS; French,PMW; de,Mello AJ (Analytical Chemistry, 2014)
Uracil DNA glycosylase plays a key role in DNA maintenance via base excision repair. Its role is to bind to DNA, locate unwanted uracil, and remove it using a base flipping mechanism. To date, kinetic analysis of this complex process has been achieved using stopped-flow analysis but, due to limitations in instrumental dead-times, discrimination of the “binding” and “base flipping” steps is compromised. Herein we present a novel approach for analyzing base flipping using a microfluidic mixer and two-color two-photon (2c2p) fluorescence lifetime imaging microscopy (FLIM). We demonstrate that 2c2p FLIM can simultaneously monitor binding and base flipping kinetics within the continuous flow microfluidic mixer, with results showing good agreement with computational fluid dynamics simulations.